Banks and sovereign risk: A granular view - Claudia M. Buch; Michael Koetter; Jana Ohls (Deutsche Bundesbank, 2013)
In this paper, we use detailed data on the sovereign debt holdings of all German banks to analyse the determinants of sovereign debt exposures and the implications of sovereign exposures for bank risk. Our main findings are as follows. First, sovereign bond holdings are heterogeneous across banks. Larger, weakly capitalised banks and banks with a small depositor base hold more sovereign bonds. Around 31% of all German banks hold no sovereign bonds at all. Second, the sensitivity of banks to macroeconomic factors increased significantly in the post-Lehman period. Banks hold more bonds from euro area countries, from low-inflation countries, and from countries with high sovereign bond yields. Third, there has been no marked impact of sovereign bond holdings on bank risk. This result could indicate the widespread absence of marking-to-market for sovereign bond holdings at the onset of the sovereign debt crisis in Europe.
Keywords: G11; G18; G21; G28; 330; sovereign debt; bank-level heterogeneity; bank risk